Seed survival and predation of Anoda cristata in soyabean crops - Puricelli, Eduardo Carlos Jose Maria (2005)
Anoda cristata is a troublesome annual broad-leaved weed in summer crops in the rolling Pampa in Argentina; seeds are the only source of regeneration of this species. Seed persistence or depletion is the result of survival and loss processes, including predation. The objective of this study was to determine survival at two burial depths in undisturbed soil and predation rates of A. cristata seeds in soyabean crops in different rotations and tillage systems. Survival was discontinuous and decreased to 25% after 35 months, after which no further reduction in survival was observed to the end of the experiment at 96 months. No differences in seed survival between seeds placed on the soil surface and buried 5 cm below the soil surface were found at 80 months, but at later times survival was lower for seeds placed on the soil surface. Predation rates ranged between 0.3% day−1 and 6.7% day−1. Of the models tested, a polynomial regression of the rate of predation with time gave the best representation of seed predation. From January to July, predation was higher in non-tillage plots in the wheat/soyabean rotation. There was no significant difference in predation rates between tillage systems in the soyabean monoculture and no difference between planting densities. Higher crop residue levels in non-tillage plots in the wheat/soyabean rotation was the dominant factor influencing seed predation, probably because such habitat favours the presence of seed predators.